Efficacy of continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea (OSA) and resistant hypertension (RH): Systematic review and meta-analysis. (August 2021) - Labarca, Gonzalo; Schmidt, Alexia; Dreyse, Jorge; Jorquera, Jorge; Enos, Daniel; Torres, Gerard; Barbe, Ferran
Summary: Approximately 70–85% of patients with resistant hypertension (RH) report obstructive sleep apnea (OSA). However, whether therapy with continuous positive airway pressure (CPAP) improves blood pressure (BP) in this population is not clear. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to determine the efficacy of CPAP in patients with OSA and RH. Two reviewers performed the literature search, risk of bias analysis, and data extraction. The pooled data were analyzed in a meta-analysis using the DerSimonian-Laird method. We calculated the mean difference (MD) in systolic blood pressure (SBP) and diastolic blood pressure (DBP) measured at 24 h and in the daytime and nighttime. We also evaluated changes in aortic stiffness and aldosterone excretion. A total of 10 RCTs and 606 participants were included. CPAP was associated with changes in 24-h SBP (−5.06 mmHg; CI, −7.98, −2.13), 24-h DBP (−4.21 mmHg; CI, −6.5, −1.93), daytime SBP (−2.34 mmHg; CI, −6.94, +2.27), daytime DBP (−2.14 mmHg; CI, −4.96, −0.67), nighttime SBP (−4.15 mmHg; CI, −7.01, −1.29), and nighttime DBP (−1.95 mmHg; CI, −3.32, −0.57). We found no benefit for aortic stiffness, but it did lead to a mild reduction in aldosterone secretion. CPAP therapy improved BP, especially nighttime BP, in this population.